Taming Europe’s digital landscape? Brief notes on the proposal for a Digital Services Act - Pereira, Miguel (UNIO – EU Law Journal, 2021)
In light of the intensive technological developments in the last two decades that we have borne witness to, the European Union is looking to modernise its framework governing the provision of digital services within the Single Market. The main regulatory instrument, in this regard, is the E-Commerce Directive enacted 20 years ago, which focuses on ensuring freedom of movement of goods and services. The evolution of the information society, towards “attention economy” services, has, however, brought to light the deficiencies of a markedly liberal approach to the Single Digital Market’s (“SDM”) Regulation. The main instrument to modernise the SDM’s Regulation is the Digital Services Act (“DSA”) which introduces new responsibilities on service providers in an attempt to better safeguard the EU citizen’s safety and fundamental rights online. In this paper, we review the Commission’s proposal for the DSA, highlighting the main novelties the instrument introduces and the main issues we have identified so far